ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI UNTUK MEMBAYAR PAJAK DENGAN KONDISI KEUANGAN DAN PREFERENSI RISIKO WAJIB PAJAK SEBAGAI VARIABEL MODERATING (STUDI KASUS PADA WAJIB PAJAK YANG TERDAFTAR DI KPP PRATAMA MALANG UTARA) - Melisa Damayanti; Abdul Wahid Mahsuni; Afifudin Afifudin (Universitas Islam Malang, 2020)
Analysis of Factors Affecting the Compliance of Individual Taxpayers to Pay Taxes with Financial Conditions and Taxpayer Risk Preferences as Moderating Variables (Case Study of Taxpayers Registered in North Malang Kpp). From the results of the analysis and discussion of Factors Affecting the Compliance of Individual Taxpayers to Pay Taxes with Financial Conditions and Taxpayer Risk Preferences as Moderating Variables in KPP Pratama Utara Malang Based on the research results, the tax required between knowledge and understanding of taxpayers regarding regulations taxation with the approval of the taxpayer. Taxpayer risk preferences moderate and significantly strengthen the relationship between taxpayer knowledge and understanding of tax regulations and taxpayer requirements. Financial requirements and preferences of taxpayers moderate and significantly strengthen the relationship between taxpayers 'knowledge and understanding of tax regulations and taxpayers' requirements. This is evidenced by the significance of the moderating variable of 0.036, which means that it is below the 0.05 significance level. Requests a relationship between taxpayer knowledge and understanding of tax regulations with significant positive taxpayer regulations after they are added. Keywords: Taxpayer Compliance, Cake Conditions, WP Knowledge, WP Understanding, WP Risk Preference